Quadratic Bezier Homotopy Function for Solving System of Polynomial Equations (MATEMATIKA, 2013)
We compare standard homotopy function with a proposed quadratic Bezier homotopy function to see which method has greater applicability and greater accuracy. We test the methods on system of polynomial equations by using Newton-Homotopy Continuation method. The results obtained indicate the superior accuracy of our proposed quadratic Bezier homotopy function. Keywords: Numerical method; Polynomial equations; Homotopy function. 2010 Mathematics Subject Classification: 65H05; 65H10; 65H20